A Ce(iii) complex potently inhibits the activity and expression of tyrosine phosphatase SHP-2. Issue 47 (25th November 2019) - Lin, Lixia; Lu, Liping; Du, Ran; Yuan, Caixia; Zhu, Miaoli; Fu, Xueqi; Xing, Shu
Abstract : Complex 3 potently inhibits the activity and expression of tyrosine phosphatase SHP-2 and decreases cellular viability. Abstract : Four new Ce(iii ) complexes 1–4 with tridentate NNO-donor Schiff base ligands have been designed and successfully synthesized. These complexes were characterized by elemental analysis, IR, and ESI-MS, with formulas of [Ce(HL1)2 (NO3 )3 ]·2CH3 OH (1 ), [Ce(L2)2 (NO3 )]·3H2 O (2 ), [Ce(HL3)(L3)(NO3 )Br]·H2 O (3 ) and [Ce(L4)2 (NO3 )]·3H2 O (4 ), in which ligands HL1–HL4 are respectively N ′-[(1 E )-pyridin-2-ylmethylidene]pyrazine-2-carbohydrazide (HL1), 2-(1-(salicyloylhydrazono)ethyl)pyrazine (HL2), N ′-[(1 E )-pyridin-2-ylmethylidene]pyridine-2-carbohydrazide (HL3) and 2-(1-(salicyloylhydrazono)ethyl) pyridine (HL4). X-ray single crystal diffraction analysis indicates that complex 1 crystallizes in the monoclinic system with the space group C 2/ c and the structure of complex 1 consists of a monomeric Ce(iii ) species with a Ce(iii ) moiety bonded to two tridentate Schiff base ligands, three nitrates and solvents. These complexes effectively inhibit the enzyme activities of PTPs (SHP-1, SHP-2, TCPTP and PTP1B), among which complex 3 shows the most potent inhibition of SHP-2 with the lowest IC50 value of 0.61 μM and displays obvious selectivity towards SHP-2. Its inhibition potency against SHP-2 was approximately 17, 4, and 5 fold higher than that against SHP-1, TCPTP and PTP1B, respectively. Further study discloses that complex 3 inhibits SHP-2 in a competitive manner. Fluorescence measurements indicate that complex 3 tightly binds to SHP-2 with a molar ratio of 1 : 1 and a binding constant of 5.45 × 10 5 M −1 . Western blot experiments show that complex 3 promotes the phosphorylation of the SHP-2 substrate by the combination of the inhibition of the activity and expression of SHP-2. Moreover, complex 3 decreases the survival rate of A549 cells to 35.12% at 100 μM and induces apoptosis with an apoptosis rate of 12.06% at 50 μM. All these results suggest that complex 3 is a potential bi-functional inhibitor of the activity and expression of tyrosine phosphatase SHP-2.